2016
DOI: 10.3747/co.23.3243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemotherapy on Health-Related Quality of Life among Early-Stage Ovarian Cancer Survivors: A Study from the Population-Based Profiles Registry

Abstract: Background There is wide variation in the application of adjuvant chemotherapy in early-stage epithelial ovarian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…As found in previous studies, patients who did not receive chemotherapy reported better global health scores compared with patients who underwent chemotherapy . This is conceivable given that the adverse effects of adjuvant chemotherapy may persist up to 1 year after treatment and only resolve later on .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As found in previous studies, patients who did not receive chemotherapy reported better global health scores compared with patients who underwent chemotherapy . This is conceivable given that the adverse effects of adjuvant chemotherapy may persist up to 1 year after treatment and only resolve later on .…”
Section: Discussionmentioning
confidence: 52%
“…As found in previous studies, patients who did not receive chemotherapy reported better global health scores compared with patients who underwent chemotherapy. 32 This is conceivable given that the adverse effects of adjuvant chemotherapy may persist up to 1 year after treatment and only resolve later on. 33,34 It has to be noted that the short-term and long-term side effects of chemotherapy may be alleviated by high-quality supportive care 35 including symptom management.…”
Section: Resultsmentioning
confidence: 99%
“…Bhugwandass CS et al (2016) assessed differences in health-related quality of life between patients with early-stage ovarian cancer who did or did not receive chemotherapy as adjuvant treatment. They found that patients who receive adjuvant chemotherapy have a significantly worse score for 3 aspects of HRQOL [17].…”
Section: Discussionmentioning
confidence: 99%
“…All these agents cause serious side effects [3] [4] [5], which includes kidney, liver, nerve and blood vessel damage, hearing loss, lower blood count etc. [6] [7], regional toxicity affecting mucosa cells, causing irritative urinary and blood loss [7]. Later toxic effects include damage to proliferating cells such as fibroblasts, endothelial and parenchymal cells [7].…”
Section: Conventional Cancer Therapymentioning
confidence: 99%
“…Later toxic effects include damage to proliferating cells such as fibroblasts, endothelial and parenchymal cells [7]. Other undesired side effects such as immune suppression, bone necrosis, lung fibrosis and skin devascularization are seen with all conventional therapies [5] [6] [7] [8]. Although the desired goal of chemotherapy is to eliminate the tumor cells, diverse range of normal cells is also affected, leading to many adverse side effects on multiple organ systems [9]- [14].…”
Section: Conventional Cancer Therapymentioning
confidence: 99%